The Infant Facial Expressions Of Emotions From Looking at Pictures. Peruvian version - Traverso Koroleff, Pierina (2012)
The Peruvian version of the Infant Facial Expression of Emotions from Looking at Pictures (IFEEL), instrument that assessed the interpretation of emotions from children’s faces pictures is presented. The original version from Emde, Osofsky & Butterfield (1993) was developed in the United States and involves 30 stimuli. The Peruvian version involves 25 pictures of children with prototypic facial features of the majority of Peruvian population. A sample of 363 men and women of middle and low socio-economic status between 19 and 45 years old was recruited to develop the Peruvian version. From the results, a lexicon was created with the words that were used by the participants to designate the 14 groups of emotion that were obtained. The majority of these groups had an adequate reliability for temporal stability. Finally, it was found that the socio-economic status (SES) is a variable that generates significant differences in the way how persons interpret the emotions. Therefore, referential values of differentiated interpretation were created from this variable.